Longer diagnosis‐to‐ablation time is associated with recurrence of atrial fibrillation after catheter ablation—Systematic review and meta‐analysis. Issue 2 (27th December 2019) - Pranata, Raymond; Chintya, Veresa; Raharjo, Sunu B.; Yamin, Muhammad; Yuniadi, Yoga
Abstract: Background: Diagnosis‐to‐ablation time (DTAT) has been postulated to be one of the predictors of atrial fibrillation (AF) recurrence, and it is a "modifiable" risk factor unlike that of many electrocardiographic or echocardiographic parameters. This development may change our consideration for ablation. In this systematic review and meta‐analysis, we aim to analyze the latest evidence on the importance of DTAT and whether they predict the AF recurrence after catheter ablation. Methods: We performed a comprehensive search on topics that assess diagnosis‐to‐ablation time (DTAT) and AF recurrence from inception up until August 2019 through PubMed, EuropePMC, Cochrane Central Database, and ClinicalTrials.gov . Results: There was a total of 3548 patients from six studies. Longer DTAT was associated with increased risk for AF recurrence in all studies included. Meta‐analysis of these studies showed that DTAT had a hazard ratio (HR) of 1.19 [1.02, 1.39], P  = .03; I 2 : 92% for AF recurrence. Upon sensitivity analysis by removing a study, HR became 1.24 [1.16, 1.32], P  < .001; I 2 : 29%. Meta‐analysis on DTAT time >3 years had HR 1.73 [1.54, 1.93], P  < .001; I 2 : 45% for the recurrence of AF. Upon subgroup analysis of data that compared >6 years to <1 year, the HR was 1.93 [1.62, 2.29], P  < .001; I 2 : 0%. Conclusion: Longer DTAT time is associated with an increased risk of AF recurrence. Hence, determining management at the earliest possible moment to avoid delay is of utmost importance. Abstract : Diagnosis‐to‐ablation time >3 years is associated with the increased risk of atrial fibrillation recurrence after catheter ablation.